Pencegahan Bahaya Narkoba dan Miras di SDI Lamalewar, Nagawutung, Lembata : Berantas Bersama, Lindungi Masa Depan - Joani Eliano Da Silva; Maria E. Uto Poton; Simon Dawa Dama Yelu; Theresa V. P. Florenso; Paulina Yoliavit Wonga; Frans Nyong; Maximianus Ardon Bidi (Politeknik Kampar, 2024)
This study examines efforts to prevent drug and alcohol abuse at SDI Lamalewar, Nagawutung, Lembata, NTT. This study was motivated by the increasing prevalence of drug abuse in the school-age group in Indonesia, which reached 2.6% (2.3 million people), as well as data from the Lembata Regency BNN which recorded 28 cases of drug abuse throughout 2022, with 15% involving children under the age of 15 years. In Nagawutung District itself, there was a 23% increase in cases of alcohol abuse with 12% of perpetrators under the age of 15 years.